Method for preparing wood nanocellulose and reinforced composite materials thereof

By using dibasic anhydride for esterification and microfibrosis treatment at low temperature, the problems of low lignin content and high energy consumption in the preparation of ligno nanocellulose in the prior art were solved, and high-performance ligno nanocellulose was prepared. And directly kneaded with the polymer matrix to simplify the process and improve the performance of the composite material.

CN116867942BActive Publication Date: 2024-12-27ZHEJIANG UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280010019.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2024-12-27
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

The method for preparing ligno nanocellulose in the prior art has problems such as low lignin content, uneven size distribution, high energy consumption and unfriendly environment, and it is difficult to directly prepare high-performance ligno nanocellulose reinforced composite materials.

Method used

Using dibasic anhydride as a pretreatment reagent, the esterification reaction is carried out at a lower temperature, and the fiber surface is grafted and carboxyl groups are dissociated through microfibrosis equipment to prepare a high lignin content, uniform size and high mechanical properties. The ligno nanocellulose is directly kneaded with the polymer matrix to prepare the composite material.

Benefits of technology

The preparation of high-performance lime nanocellulose under mild and low energy consumption conditions is achieved, which simplifies the process and improves the dispersion of LCNF in polymer matrix and the mechanical properties of composite materials, including higher UV resistance and barrier properties. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004336642700000131
    Figure BDA0004336642700000131
  • Figure BDA0004336642700000141
    Figure BDA0004336642700000141
  • Figure BDA0004336642700000191
    Figure BDA0004336642700000191
Patent Text Reader

Abstract

The present invention relates to a method for preparing wood nanocellulose and wood nanocellulose prepared by the method. The present invention also relates to a method for preparing a wood nanocellulose-reinforced composite material and a wood nanocellulose-reinforced composite material prepared by the method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing wood nanocellulose and wood nanocellulose prepared by the method. The present invention also relates to a method for preparing a wood nanocellulose-reinforced composite material and a wood nanocellulose-reinforced composite material prepared by the method. Background Art

[0002] Cellulose Nanofibril (CNF) is an excellent environmentally friendly nanomaterial due to its high mechanical strength, high aspect ratio and biodegradability. However, traditional CNF is difficult to disperse evenly and easily aggregates in hydrophobic polymer matrices such as polyester due to its rich hydrophilic hydroxyl groups on the surface, which increases the processing difficulty and greatly reduces the mechanical properties of the resulting composite material.

[0003] Lignin is the second largest natural polymer after cellulose, and has the characteristics of hydrophobicity, antibacterial, UV resistance, and high thermal stability.

[0004] Wood nanocellulose (LCNF) is a nanocellulose containing lignin, which has the advantages of both CNF and lignin. Its preparation method omits the step of removing lignin included in the preparation of CNF and thus eliminates the required toxic chemical reagents and a large amount of energy consumption, thereby making the utilization rate of biomass raw materials higher and more in line with the requirements of green environmental protection in modern society. It has a good prospect in industrial promotion and practical application.

[0005] At present, the methods for preparing LCNF mainly include mechanical dissociation, such as high-pressure homogenization, grinding, microfluidization, etc., usually combined with pretreatment methods such as ultrasound, acid, alkali, organic solvents or enzymes. The common problems existing in these prior art methods are that the prepared LCNF has a low lignin content (<10%), uneven size distribution (diameter 5-1000nm), and a short length (<650nm); moreover, the pretreatment step in the preparation method needs to be carried out at high temperature (≥120°C), which leads to high energy consumption and environmental unfriendliness.

[0006] “A comparative study of energy consumption and physical properties of microfibrillated cellulose produced by different processing methods”, Spence et al., Cellulose, 2011, No. 18, pp. 1097-1111, reported that using kraft pulp containing 2.4% lignin as raw material, after pulping pretreatment, it was homogenized by a microfluidizer 20 times to prepare LCNF with a diameter of <1 μm, so the energy consumption was high. “Effect of high residual lignin on the thermal stability of nanofibrils and its enhanced mechanical performance in aqueous environments”, Nair et al., Cellulose, 2015, No. 22, pp. 3137-3150, reported that using pine bark as raw material, after NaOH and NaClO pretreatment, it was ground 15 times by a grinder to prepare LCNF with a lignin content of 5.2% and a diameter of about 50 nm; however, when the lignin content increased to 21.3%, its diameter reached 100 nm. "Preparation and evaluation of high-lignin content cellulose nanofibrils from eucalyptus pulp", Herrera et al., Cellulose, 2018, No. 25, pp. 3121-3133 reported that chemical mechanical pulp was used as raw material, 2,2,6,6-Tetramethylpiperidinyloxy (TEMPO) was used as a medium, and oxidative pretreatment was carried out in a NaBr and NaClO system, and then LCNF with a high lignin content (23%) was prepared by homogenization with a microjet high-pressure homogenizer; however, the obtained LCNF was uneven in size and contained a large number of micron-sized particles, and TEMPO was a non-green chemical."Comprehensive elucidation of the effect of residual lignin on the physical, barrier, mechanical and surface properties of nanocellulose films", Rojo et al., Green Chem., 2015, No. 17, pp. 1853-1866 reported that using Norway spruce fiber as raw material, after pretreatment with SO2 at 135-155°C, LCNF with a lignin content of 1.7-11.5% and a diameter of 20-44 nm was obtained by homogenizing it 6 times with a microfluidizer; although the energy consumption of preparing LCNF is reduced and the diameter becomes smaller after SO2 steam pretreatment, the pretreatment process is costly and SO2 will cause environmental pollution. "A novel method to prepare lignocellulose nanofibrils directly from bamboo chips", Liu et al., Cellulose, 2018, Issue 25, Pages 7043-7051 reported that bamboo was used as raw material, glycerol was used for pretreatment at 120°C for 2 hours, and then screw extrusion and grinding were performed to obtain LCNF with a diameter of 20-100 nm. However, the size distribution of the obtained LCNF was uneven, the solution stability was poor, and it was easy to agglomerate. "Producing wood-based nanomaterials by rapid fractionation of wood at 80℃using a recyclable acid hydrotrope", JYZhu, Green Chem., 2017, No. 19, pp. 3370-3379 reported that after pretreatment with organic acid (p-toluenesulfonic acid), LCNF with a lignin content of 7-16% and a diameter of 15-51nm can be prepared by microfluidization homogenization 4-13 times. However, the size of the obtained LCNF is uneven, and the pretreatment temperature is as high as 165℃, which will lead to the condensation of lignin and the degradation of cellulose, thereby reducing the utilization rate of raw materials.

[0007] Based on this, the problems existing in the methods for preparing LCNF in the prior art can be summarized as follows: (1) most of them are based on unbleached pulp fibers, and the yield calculated from the real raw materials is <50%; (2) the pretreatment process is not environmentally friendly and the entire preparation process has high energy consumption; and (3) it is impossible to simultaneously obtain LCNFs with high lignin content (>15%), high aspect ratio (diameter <20 nm and length >1000 nm) and long-term solution stability (high surface charge).

[0008] In summary, in the existing technology, it is still a huge challenge to prepare LCNF with high lignin content, uniform size and high mechanical properties under mild conditions, environmentally friendly and low energy consumption.

[0009] In addition, in the process of using LCNF as a filler to prepare reinforced composite materials, in order to fully mix LCNF and the polymer matrix, a special solvent system is generally required as a good solvent, or complex mechanical blending is required. For example, "Thermal, Mechanical, and Degradation Properties of Nanocomposites Prepared using Lignin-Cellulose Nanofibers and Poly (Lactic Acid)", Wang et al., BioRes, 2014, No. 9, pp. 3211-3224 reported that DMAc was used as a good solvent to mix LCNF and PLA. "Reinforcement of polycaprolactone with microfibrillated lignocellulose", Herzele et al., Industrial Crops and Products, 2016, No. 93, pp. 302-308 reported that the LCNF needs to be solvent-exchanged into acetone and toluene first to achieve the dispersion of LCNF in the polycaprolactone matrix. "Preparation and Characterization of Polybutylene Succinate Reinforced with Pure Cellulose Nanofibril and Lignocellulose Nanofibril Using Two-Step Process", Cindradewi et al., Polymers, 2021, Issue 13, Page 3945 reported that NMP was used as a good solvent for blending LCNF and polybutylene succinate (PBS). If this type of highly toxic organic solvent is not used, a complex mechanical blending method is required. For example, "Flame retardance-donated lignocellulose nanofibers (LCNFs) by the Mannichreaction with (amino-1,3,5-triazinyl) phosphoramidates and their properties", Ono et al., RSC Adv., 2022, Issue 12, Page 3300 reported that a high-energy grinder and an internal mixer were used successively to achieve good premixing of LCNF and PP pellets.

[0010] In summary, the problem with the method of preparing LCNF-reinforced composite materials in the prior art is that it is impossible to directly prepare LCNF-reinforced composite materials. Instead, as mentioned above, LCNF needs to be prepared first, and then a solvent exchange or complex mechanical blending process is performed to achieve premixing with a polymer matrix, and then subsequent processing is performed. Therefore, the process is complicated and the dispersibility of LCNF in the polymer matrix is ​​general.

[0011] Therefore, it is necessary to develop a method for preparing LCNF and a method for preparing LCNF-reinforced composites that can overcome the above-mentioned defects.

[0012] BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Attached Figure 1 is a TEM image of the LCNF prepared in Example 1-1.

[0014] Attached Figure 2 is a TEM image of the LCNF prepared in Example 1-2.

[0015] Attached Figure 3 is a TEM image of the LCNF prepared in Example 1-4.

[0016] Attached Figure 4 is a TEM image of the LCNF prepared in Example 1-5.

[0017] Attached Figure 5 is a TEM image of the LCNF prepared in Example 1-6.

[0018] Attached Figure 6 is a TEM image of the LCNF prepared in Example 1-7.

[0019] Attached Figure 7 is a TEM image of the LCNF prepared in Example 1-8.

[0020] Attached Figure 8 is a TEM image of the LCNF prepared in Comparative Example 1-1.

[0021] Attached Fig. 9 is a TEM image of the LCNF prepared in Comparative Example 1-2.

[0022] Attached Fig.10 This is a SEM photo of the cross section of the LCNF-enhanced PBAT composite film prepared in Example 2-2

[0023] Attached Fig.11 This is a SEM photograph of the cross-section of the LCNF reinforced PBAT composite film prepared in Comparative Example 2-1.

[0024] Attached Fig.12This is a SEM photograph of the cross section of the pure PBAT film without LCNF filler prepared in Comparative Example 2-7. Summary of the invention

[0025] The purpose of the present invention is to provide a method for preparing wood nanocellulose in a mild, environmentally friendly and low-energy consumption manner in view of the problems existing in the prior art. The method uses a dibasic acid anhydride as a pretreatment agent, and at a relatively low temperature (≤120°C), allows different types of biomass raw materials to undergo an esterification reaction, thereby grafting a large number of carboxyl groups on the fiber surface, increasing the repulsion between fibers in an aqueous solution, and thus can prepare wood nanocellulose with improved performance in a mild, environmentally friendly and low-energy consumption manner.

[0026] In one aspect, the present invention provides a method for preparing wood nanocellulose, comprising:

[0027] (1) dispersing a biomass raw material in a dibasic acid anhydride and about 0-5% water, performing an esterification pretreatment reaction at a temperature below 120° C. to obtain a pretreatment reaction product, and washing the pretreatment reaction product to neutrality to obtain a neutral pretreatment reaction product; and

[0028] (2) dispersing the neutral pretreatment reaction product in a medium and performing a dissociation treatment using a microfibrillation device to obtain a dispersion of wood nanocellulose.

[0029] In the esterification pretreatment reaction of (1) above, the temperature used is critical and needs to be controlled below 120°C, preferably about 20-120°C, more preferably about 60-110°C, and most preferably about 80-100°C; the pressure conditions used are usually about 1-10 bar, preferably about 1-3 bar; the pretreatment time is usually about 0.5-24 hours, preferably about 1-5 hours.

[0030] The biomass raw materials are those known in the art, generally including but not limited to wood (e.g., coniferous wood, broad-leaved wood), gramineous plants, crop straw, husks, pine cones, plant residues (e.g., bagasse, coffee bean residues), etc. Preferred biomass raw materials used in the method of the present invention include, for example, pine, cypress, fir, eucalyptus, poplar, birch, bamboo, rice straw, corn straw, wheat straw, sorghum straw, reed, peanut shells, rice husks, pine cones, bagasse, coffee bean residues, etc. In the present invention, one biomass raw material or a mixture of two or more biomass raw materials can be used.

[0031] The dibasic acid anhydride is one commonly used in the art, including, for example, malonic anhydride, maleic anhydride (maleic anhydride), dimethylmaleic anhydride, fumaric anhydride, succinic anhydride, methylsuccinic anhydride, 2-hydroxysuccinic anhydride, (2-propylene)succinic anhydride, S-acetylmercaptosuccinic anhydride, cis-3-carboxyglutarate anhydride, trans-1,2-cyclohexanedicarboxylic anhydride, glutaric anhydride, adipic anhydride, cis-4-cyclohexene -1,2-dicarboxylic anhydride, cyclohexane-1,2-dicarboxylic anhydride, pimelic anhydride, suberic anhydride, azelaic anhydride, dodecyl succinic anhydride, dodecenyl succinic anhydride, phthalic anhydride, 4-chlorophthalic anhydride, tetrachlorophthalic anhydride, 3-fluorophthalic anhydride, 3,6-difluorophthalic anhydride, tetrafluorophthalic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride and citric anhydride, etc. In the method of the present invention, the preferred dibasic acid anhydride is selected from maleic anhydride, succinic anhydride, glutaric anhydride and phthalic anhydride. In the present invention, a dibasic acid anhydride or a mixture of multiple dibasic acid anhydrides can be used.

[0032] The ratio (weight ratio) of the biomass raw material to the dibasic acid anhydride is generally about 5:1-1:100, preferably about 1:1-1:50, and more preferably about 1:4-1:20.

[0033] In the esterification pretreatment reaction of (1) above, in addition to the dibasic acid anhydride, about 0-5% of water, preferably about 0-2% of water, based on the total weight of the biomass raw material, the dibasic acid anhydride and the water may also be added. In the method of the present invention, preferably, no water is present in the esterification pretreatment reaction, that is, the esterification pretreatment reaction is carried out in an anhydrous system. Wherein, the water includes the water contained in the raw material and the additionally added water, so the water content refers to the sum of the water contained in the raw material and the additionally added water. Therefore, in the absence of water in the esterification pretreatment reaction, all raw materials are dry and do not contain water.

[0034] The washing step is known in the art and can be carried out by using water or an alkali solution, wherein the alkali solution is an aqueous solution of an alkali known in the art, which is used to wash away the residual anhydride and reaction by-products in the pretreatment reaction product to obtain a neutral pretreatment reaction product. The alkali includes, for example, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, sodium bisulfate, potassium bisulfate, sodium monohydrogen phosphate and potassium monohydrogen phosphate. The concentration of the alkali solution is generally about 0.1-40%.

[0035] In the above-mentioned (2) dissociation step, the medium includes water or an aqueous solution of a high molecular weight polymer, preferably water. The high molecular weight polymer is one commonly used for dissociating biomass raw materials, including, for example, polyvinyl alcohol, polyethylene glycol, starch, starch derivatives such as carboxymethyl starch and acetic starch, chitosan, chitin, hydroxymethyl cellulose, carboxymethyl cellulose, polyacrylamide (PAM), hydrolyzed polyacrylamide (HPAM) and pyrrolidone (PVP) and the like. The high molecular weight polymer is preferably polyvinyl alcohol, starch, starch derivatives, chitosan, chitin and carboxymethyl cellulose. The concentration of the high molecular weight polymer in its aqueous solution is usually about 0.01-60%.

[0036] The relative amounts of the neutral pre-treatment reaction product and the vehicle can vary within a wide range, and are generally in a weight ratio of about 0.01:100-10:100, preferably about 0.05:100-10:10.

[0037] Further, the method of the present invention comprises an optional step (3): further drying the dispersion of wood nano cellulose obtained in step (2) to remove the medium therein to obtain a powder of wood nano cellulose. In this case, the medium is usually water or starch and its derivatives. The powder of wood nano cellulose can be easily redispersed in the medium to form a stable dispersion.

[0038] The microfibrillation equipment is known in the art, including, for example, ultrasonic instruments, high-pressure homogenizers, ball mills, disc grinders, microfluidizers, stirrers, ice breakers, etc. The conditions for dissociation using microfibrillation equipment are also known in the art, for example, the temperature is usually room temperature; in the case of using a stirrer or an ice breaker, the stirring speed is usually about 5000-40000 rpm; in the case of using a high-pressure homogenizer, the piston spacing is usually about 50-500 μm, and the pressure is usually about 10-500 MPa; in the case of using an ultrasonic instrument, the power is usually about 500-2000 W; in the case of using a microfluidizer, the pipe diameter is usually about 50-500 μm, and the pressure is usually about 10-800 MPa.

[0039] The dispersion or powder of wood nanocellulose obtained by the method of the present invention shows one or more improved properties and an excellent comprehensive performance balance, wherein the improved properties include high lignin content (which means higher hydrophobicity and higher yield), high surface charge (which means better long-term stability of the solution and better dissociation performance), high thermal decomposition temperature (which means a higher processing temperature window when mixed with a polymer matrix to prepare a composite material, and better thermal stability of the end product), longer length and finer diameter (thus higher aspect ratio) (which means that the formed network cross-linked structure has a lower percolation threshold, thereby obtaining higher mechanical properties). Typically, the resulting dispersion or powder of wood nanocellulose has: a lignin content of about 10-40%, preferably about 15-40% and more preferably about 15-25%, a surface charge of about 300-3000 μmol / g, preferably about 600-2000 μmol / g, a thermal decomposition temperature of greater than about 200° C., preferably greater than about 240° C., a length of about 500-5000 nm, preferably about 1000-5000 nm, a diameter of about 3-20 nm, preferably about 3-10 nm, and an aspect ratio of about 50-1000, preferably about 100-1000.

[0040] Therefore, in another aspect, the present invention relates to a dispersion or powder of wood nanocellulose, characterized by having one or more of the following improved properties: a lignin content of about 10-40%, preferably about 15-40% and more preferably about 15-25%, a surface charge of about 300-3000 μmol / g, preferably about 600-2000 μmol / g, a thermal decomposition temperature above about 200°C, preferably above about 240°C, a length of about 500-5000 nm, preferably about 1000-5000 nm, a diameter of about 3-20 nm, preferably about 3-10 nm, and an aspect ratio of about 50-1000, preferably about 100-1000.

[0041] The dispersion of wood nanocellulose having the above-mentioned improved properties can be used in those applications in which wood nanocellulose is commonly used, especially in the preparation of films, papermaking wet additives, gel raw materials, coatings, etc.

[0042] The wood nanocellulose powder with the above-mentioned improved properties can be used as a filler in polymer composite materials to improve the properties of the composite materials, including, for example, mechanical properties, UV resistance, barrier properties and degradation properties.

[0043] In another aspect, the present invention provides a method for preparing a wood nanocellulose reinforced composite material, comprising:

[0044] (1) dispersing a biomass raw material in a dibasic acid anhydride and about 0-5% water, performing an esterification pretreatment reaction at a temperature below 120° C. to obtain a pretreatment reaction product, and washing the pretreatment reaction product to neutrality to obtain a neutral pretreatment reaction product; and

[0045] (2) drying the neutral pretreatment reaction product and mixing it with a polymer matrix to obtain a wood nanocellulose reinforced composite material.

[0046] The esterification pretreatment reaction in the above step (1) is the same as the step (1) in the above method for preparing wood nanocellulose.

[0047] The drying in step (2) is carried out by a conventional drying process, for example, the drying process includes freeze drying, atmospheric pressure drying, evaporative drying, and spray drying. It is known to those skilled in the art that different drying methods have different drying conditions. Generally, in freeze drying, the temperature is usually about -30°C to 60°C, and the time is usually about 12-48 hours; in evaporative drying, the temperature is usually about 60-100°C, and the time is usually about 1-5 hours.

[0048] The polymer matrix is ​​known in the art. Suitable examples in the method of the present invention include, for example, polyethylene glycol (PEG), polyvinyl alcohol (PVA), polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), polybutylene succinate-adipate (PBSA), poly-ε-caprolactone (PCL), polymethylethylene carbonate (PPC), polyglycolic acid (PGA), polybutylene succinate-co-butylene terephthalate (PBST), poly(ethylene succinate-co-butylene terephthalate). - ethylene terephthalate (PEST), polyethylene succinate (PES), polyurethane (PU), polyamide (PA), polycarbonate (PC), polyoxymethylene (POM), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), polydiallyl terephthalate (PDAP), polyparaben (PHB) and polyacrylonitrile (PAN). Preferred polymer matrices include polybutylene adipate terephthalate, polylactic acid and polyurethane. In the method of the present invention, a mixture of one or more polymer matrices can be used.

[0049] The amount of the dried pretreatment reaction product in the polymer matrix is ​​generally about 0.05-20%, preferably about 0.05-5%, based on the total weight of the dried pretreatment reaction product and the polymer matrix.

[0050] The mixing can be carried out using equipment known in the art, such as a high-speed mixer, a screw extruder, an internal mixer, etc. The mixing process conditions are also conventional, usually at a temperature of about 40-250° C. and conventional pressure for about 1-30 minutes.

[0051] The advantages of the method for preparing wood nanocellulose reinforced composite materials of the present invention are that LCNF reinforced composite materials can be directly prepared (i.e., the esterified pretreated biomass raw materials are in-situ dissociated into LCNF during the mixing process with the polymer matrix), without the need for the complicated process of first preparing LCNF and then mixing it with the polymer matrix through complicated steps as in the prior art, which obviously simplifies the process and reduces energy consumption, while improving the dispersibility of LCNF in the polymer matrix, and thus preparing a composite material with improved performance, including higher mechanical properties (such as modulus, strength and toughness), higher UV resistance, higher barrier properties (water barrier, gas barrier), and better or controllable degradation performance.

[0052] Therefore, on the other hand, the present invention also relates to a wood nanocellulose reinforced composite material, characterized by having one or more of the following improved properties: higher mechanical properties (such as modulus, strength and toughness), higher UV resistance, higher barrier properties (water barrier, gas barrier), better or controllable degradation performance.

[0053] The wood nanocellulose reinforced composite material can be used in those applications where conventional wood nanocellulose reinforced composite materials are commonly used, especially in applications such as ground films, plastic bags, packaging films, cling films, straws, plastic containers, etc. Example

[0054] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0055] Unless otherwise stated, the raw materials and equipment used in the examples are commercially available conventional products. Unless otherwise stated, the temperature and pressure conditions used refer to normal temperature and pressure.

[0056] Example 1-1: Preparation of wood nanocellulose (LCNF) and its film

[0057] 5 g of dried bamboo powder was added to 25 g of maleic anhydride, and the esterification pretreatment reaction was carried out at 95 ° C and 1 bar for 3 hours; then, a large amount of deionized water was added to the reaction system to terminate the reaction, and a small amount of sodium hydroxide aqueous solution was used to wash the obtained pretreatment reaction product to neutrality. Then, a high-speed stirrer was used at 8000 rpm to perform mechanical dissociation in water for 5 minutes to obtain a dispersion of LCNF.

[0058] The morphology of LCNF after phosphotungstic acid staining was observed under a transmission electron microscope (TEM), see Appendix Figure 1 .

[0059] The LCNF dispersion was diluted with water to a concentration of 0.05%, and then formed into a film by suction filtration. The film was dried at 90° C. for 15 minutes by hot pressing to obtain a LCNF film with a dry film thickness of 30 μm.

[0060] Example 1-2: Preparation of LCNF and its film

[0061] The above Example 1-1 was repeated, except that water was additionally added in the esterification pretreatment reaction, that is, 5 g of dry bamboo powder was added to a mixture of 25 g of maleic anhydride and 0.5 g of water.

[0062] The morphology of LCNF after phosphotungstic acid staining was observed under a transmission electron microscope, see Appendix Figure 2 .

[0063] Example 1-3: Preparation of LCNF

[0064] 5 g of dried bamboo powder was added to a mixture of 25 g of maleic anhydride and 0.5 g of water, and the esterification pretreatment reaction was carried out at 95 ° C and 1 bar for 3 hours; after that, a large amount of deionized water was added to the reaction system to end the reaction, and the sample was washed with a small amount of sodium hydroxide to neutrality. Then, a high-speed stirrer was used at 8000 rpm to perform mechanical dissociation in a 50% polyvinyl alcohol aqueous solution for 5 minutes to obtain a dispersion of LCNF.

[0065] Examples 1-4: Preparation of LCNF

[0066] 5 g of dried bamboo powder was added to a mixture of 30 g of maleic anhydride and 0.5 g of water, and the esterification pretreatment reaction was carried out at 95 ° C and 1 bar for 4 hours; then, a large amount of deionized water was added to the reaction system to terminate the reaction, and a small amount of potassium hydroxide aqueous solution was used to wash the obtained pretreatment reaction product to neutrality. Then, a high-speed stirrer was used at 8000 rpm in water to perform mechanical dissociation for 5 minutes to obtain a dispersion of LCNF.

[0067] The morphology of LCNF after phosphotungstic acid staining was observed under a transmission electron microscope, see Appendix Figure 3 .

[0068] Examples 1-5: Preparation of LCNF

[0069] 5 g of dry pine wood powder was added to 50 g of succinic anhydride, and the esterification pretreatment reaction was carried out at 110 ° C and 2 bar for 2 hours; then, a large amount of deionized water was added to the reaction system to terminate the reaction, and a small amount of sodium hydroxide aqueous solution was used to wash the obtained pretreatment reaction product to neutrality. Then, a high-speed stirrer was used at 8000 rpm in water to perform mechanical dissociation for 5 minutes to obtain a dispersion of LCNF.

[0070] The morphology of LCNF after phosphotungstic acid staining was observed under a transmission electron microscope, see Appendix Figure 4 .

[0071] Examples 1-6: Preparation of LCNF

[0072] The above Examples 1-5 were repeated, except that water was additionally added in the pretreatment reaction, that is, 5 grams of dry pine wood powder was added to a mixture of 50 grams of succinic anhydride and 0.5 grams of water.

[0073] The morphology of LCNF after phosphotungstic acid staining was observed under a transmission electron microscope, see Appendix Figure 5 .

[0074] Example 1-7: Preparation of LCNF

[0075] 5 g of dried corn stalk powder was added to 75 g of dodecyl succinic anhydride, and the esterification pretreatment reaction was carried out at 80 ° C and 5 bar for 5 hours; then, a large amount of deionized water was added to the reaction system to end the reaction, and the obtained pretreatment reaction product was washed with a large amount of water until neutral. Then, a high-pressure homogenizer was used with a piston spacing of 200-500 μm, and mechanical dissociation was carried out in water for 2 times, each time for 5 minutes, to obtain a dispersion of LCNF.

[0076] The morphology of LCNF after phosphotungstic acid staining was observed under a transmission electron microscope, see Appendix Figure 6 .

[0077] Example 1-8: Preparation of LCNF

[0078] 5 grams of dried bamboo powder was added to 100 grams of tetrahydrophthalic anhydride, and 1 gram of water was added, and the esterification pretreatment reaction was carried out at 110°C and 2 bar for 3 hours; then, a large amount of deionized water was added to the reaction system to terminate the reaction, and the obtained pretreatment reaction product was washed with a small amount of potassium hydroxide aqueous solution to neutrality. Then, a high-speed stirrer was used at 8000 rpm in water to perform mechanical dissociation for 5 minutes to obtain a dispersion of LCNF.

[0079] The morphology of LCNF after phosphotungstic acid staining was observed under a transmission electron microscope, see Appendix Figure 7 .

[0080] Example 1-9: Preparation of LCNF powder

[0081] The LCNF dispersion obtained in Example 1-2 was dried in vacuo at -40°C for 24 hours using freeze drying to obtain LCNF powder.

[0082] Comparative Example 1-1: Preparation of LCNF and its film

[0083] The above Example 1-1 was repeated except that the temperature in the esterification pretreatment reaction was 130°C.

[0084] The morphology of LCNF after phosphotungstic acid staining was observed under a transmission electron microscope, see Appendix Figure 8 .

[0085] Comparative Example 1-2: Preparation of LCNF and its film

[0086] The above-mentioned Example 1-2 was repeated, except that water was additionally added in the esterification pretreatment reaction, that is, 5 g of dry bamboo powder was added to a mixture of 25 g of maleic anhydride and 2.0 g of water.

[0087] The morphology of LCNF after phosphotungstic acid staining was observed under a transmission electron microscope, see Appendix Fig. 9 .

[0088] Example 1-10: Testing the performance of LCNF

[0089] In this example, the lignin content, surface charge and morphology characteristics of the LCNF dispersions prepared in Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-2 were tested respectively.

[0090] The test method is as follows.

[0091] Lignin content determination: Tested in accordance with the Chinese Agricultural Biomass Raw Materials Cellulose, Hemicellulose, and Lignin Determination Standard (NY / T 3494-2019).

[0092] Surface charge determination: potentiometric titration. Specifically, ion exchange resin is used for sufficient exchange so that all carboxyl groups on the surface of nanocellulose exist in the form of -COOH, and then a 0.1 mol / L NaOH standard solution is used to titrate the LCNF dispersion of known concentration, and a conductivity meter is used to continuously measure the conductivity change during the titration process, and the titration endpoint is determined based on the sudden change in slope.

[0093] Thermal decomposition temperature (Tonset ): Tested by thermogravimetric analyzer (TG) in nitrogen atmosphere.

[0094] Morphological characteristics: LCNF diameter and length were measured using transmission electron microscopy (TEM) or atomic force microscopy.

[0095] (AFM).

[0096] The test results are shown in Table 1 below.

[0097] Table 1

[0098]

[0099] The above results show that:

[0100] Through the method of the present invention, wood, bamboo and crop straw can be used to prepare high lignin content and high charge

[0101] The LCNF has a large amount of LCNF, a long length and a small diameter, and a thermal decomposition temperature of ≥270°C, which broadens the range of biomass raw materials that can be effectively utilized;

[0102] Adding a small amount of water can promote the hydrolysis of dibasic acid anhydride, increase the charge in LCNF, and obtain LCNF with finer diameter;

[0103] Pretreatment temperatures of 30-120°C can lead to LCNFs with significantly improved diameter, length, and lignin content.

[0104] These improved properties are very important for LCNF as filler; while temperatures above 120 °C lead to a coarsening of the diameter, which may be because high temperature conditions cause the lignin to be removed and condensed and agglomerated on the surface of cellulose, hindering the depolymerization of the fiber.

[0105] Examples 1-11: Testing the performance of LCNF films

[0106] In this example, the mechanical properties of the LCNF films prepared in Examples 1-1 and 1-2 and Comparative Examples 1-1 and 1-2 were tested respectively.

[0107] The mechanical properties of the film were measured using a 3345 tensile tester (Instron, USA) according to GB / T 1040.3-2006. The actual thickness of the test specimens was measured by a CT-100 thickness gauge. At least 7 specimens were prepared for each group and the average value was taken. The tensile rate of the test was 2.5 mm / min.

[0108] The test results are shown in Table 2 below.

[0109] Table 2

[0110]

[0111] The above results show that the mechanical properties of the LCNF films prepared in Examples 1-1 and 1-2 of the present invention are significantly better than those of Comparative Examples 1-1 and 1-2, because the LCNF prepared in the present invention has a smaller and more uniform diameter and a longer length, so that the prepared film structure is more compact. In particular, since the diameter of the LCNF in Comparative Example 1-1 is large and uneven, the film mechanical properties are the worst; although the diameter of the LCNF in Comparative Example 1-2 is close to that of Example 1-2, due to its shorter length, the LCNF network structure constructed inside the film is poor, so the mechanical properties are poor.

[0112] Example 2-1: Preparation of LCNF-reinforced PBAT composite film

[0113] 5 grams of dried bamboo powder was added to 25 grams of maleic anhydride, and the esterification pretreatment reaction was carried out at 95°C and 1 bar for 3 hours; after that, a large amount of deionized water was added to the reaction system to terminate the reaction, and the obtained pretreatment reaction product was washed with a small amount of sodium hydroxide aqueous solution to neutrality. Then, a freeze dryer was used to vacuum dry at a temperature of -40°C for 24 hours; and 1 weight % of the dried product was added to PBAT, and a twin-screw extruder was used to mix and extrude at 150°C and 100rpm to obtain a LCNF-reinforced PBAT composite material.

[0114] The composite material was dissolved in chloroform (the solid-liquid ratio of the composite material to chloroform was 1:10), and cast into a film. The solvent was then evaporated to obtain a composite material film with a dry film thickness of 30 μm.

[0115] Example 2-2: Preparation of LCNF-reinforced PBAT composite film

[0116] Example 2-1 was repeated, except that water was additionally added in the esterification pretreatment reaction, that is, 5 g of dry bamboo powder was added to a mixture of 25 g of maleic anhydride and 0.5 g of water.

[0117] The cross-section of the prepared composite film was observed using a scanning electron microscope (SEM). Fig.10 .

[0118] Example 2-3: Preparation of LCNF-reinforced PBAT composite film

[0119] 5 grams of dried corn stalks were added to 75 grams of dodecyl succinic anhydride, and the esterification pretreatment reaction was carried out at 80°C and 5 bar for 5 hours; after that, a large amount of deionized water was added to the reaction system to end the reaction, and washed with a large amount of water until neutral. Then, a freeze dryer was used for vacuum drying at -40°C for 24 hours; and 1 weight % of the dried product was added to PBAT, and a twin-screw extruder was used to mix and extrude at 150°C and 100rpm to obtain a LCNF-reinforced PBAT composite material.

[0120] The composite material was dissolved in chloroform (the solid-liquid ratio of the composite material to chloroform was 1:10), and cast into a film. The solvent was then evaporated to obtain a composite material film with a dry film thickness of 30 μm.

[0121] Example 2-4: Preparation of LCNF-reinforced PBAT composite film

[0122] 5 grams of dry pine powder was added to a mixture of 50 grams of succinic anhydride and 0.5 grams of water, and the esterification pretreatment reaction was carried out at 110°C and 2 bar for 2 hours; after that, a large amount of deionized water was added to the reaction system to terminate the reaction, and the obtained pretreatment reaction product was washed with a small amount of sodium hydroxide aqueous solution to neutrality. Then, a freeze dryer was used for vacuum drying at -40°C for 24 hours, and 1 weight % of the dried product was added to PBAT, and a twin-screw extruder was used to mix and extrude at 150°C and 100rpm to obtain a LCNF-reinforced PBAT composite material.

[0123] The composite material was dissolved in chloroform (the solid-liquid ratio of the composite material to chloroform was 1:10), and cast into a film. The solvent was then evaporated to obtain a composite material film with a dry film thickness of 30 μm.

[0124] Example 2-5: Preparation of LCNF-reinforced PBAT composite film

[0125] 5 grams of dried bamboo powder was added to a mixture of 30 grams of maleic anhydride and 0.5 grams of water, and the esterification pretreatment reaction was carried out at 95°C and 1 bar for 4 hours; after that, a large amount of deionized water was added to the reaction system to terminate the reaction, and the obtained pretreatment reaction product was washed with a small amount of potassium hydroxide aqueous solution to neutrality. Then, a freeze dryer was used for vacuum drying at -40°C for 24 hours, and 1 weight % of the dried product was added to PBAT, and a twin-screw extruder was used to mix and extrude at 150°C and 100rpm to obtain a LCNF-reinforced PBAT composite material.

[0126] The composite material was dissolved in chloroform (the solid-liquid ratio of the composite material to chloroform was 1:10), and cast into a film. The solvent was then evaporated to obtain a composite material film with a dry film thickness of 30 μm.

[0127] Example 2-6: Preparation of a film of a composite material of LCNF and polylactic acid

[0128] Example 2-1 was repeated except that polylactic acid was used instead of PBAT.

[0129] Example 2-7: Preparation of LCNF and polyurethane composite film

[0130] Example 2-1 was repeated except that polyurethane was used instead of PBAT.

[0131] Comparative Example 2-1: Preparation of a comparative LCNF-reinforced PBAT composite film

[0132] The above Example 2-1 was repeated, except that the temperature used in the esterification pretreatment reaction was 130°C.

[0133] The cross section of the prepared composite film was observed by SEM, see Appendix Fig.11 .

[0134] Comparative Example 2-2: Preparation of a comparative LCNF-reinforced PBAT composite film

[0135] The above Example 2-1 was repeated, except that water was additionally added in the esterification pretreatment reaction, that is, 5 g of dry bamboo powder was added to a mixture of 25 g of maleic anhydride and 2.0 g of water.

[0136] Comparative Example 2-3: Preparation of a comparative LCNF-reinforced PBAT composite film

[0137] 1% by weight of the LCNF powder obtained in Examples 1-8 was added to PBAT, mixed uniformly and extruded using a twin-screw extruder at 150° C. and 100 rpm to obtain a LCNF-reinforced PBAT composite material.

[0138] The PBAT / LCNF composite material was then dissolved in chloroform (the solid-liquid ratio of the composite material to chloroform was 1:10) and cast into a film, and then the solvent was evaporated to obtain a film of the composite material with a dry film thickness of 30 μm.

[0139] Comparative Example 2-4: Preparation of a comparative CNF-reinforced PBAT film

[0140] In this comparative example, a CNF-enhanced PBAT film of the prior art was prepared, and the preparation method thereof was as follows: 10 g of bamboo powder was treated with peracetic acid at a concentration of 4 wt % at 85° C. and a solid-liquid ratio of 1:5 for 45 minutes to remove lignin therein, and the process was repeated 3-4 times until the bamboo powder was completely bleached; then, the bamboo powder was washed with a large amount of deionized water to neutrality; then, 5 g of the bleached bamboo powder was dispersed in 450 ml of sodium acetate buffer solution (pH=6.8), and CNF was prepared by 2,2,6,6-tetramethylpiperidinyl oxide (TEMPO) oxidation method, wherein the mass ratio of bamboo powder: TEMPO: sodium bromide was 1:0.016:0.16; then, a certain amount of sodium hypochlorite solution (15 mmol / g bamboo powder) was added, and the pH of the reaction solution was maintained at 10.5 by titration with NaOH solution, and the reaction was carried out at room temperature for 2 hours; after the reaction, the sample was washed with a large amount of deionized water to neutrality, and then mechanically exfoliated using a high-speed stirrer to obtain a CNF solution.

[0141] The CNF solution was freeze-dried, and then 1 wt % of the dried CNF was added to the PBAT, mixed uniformly and extruded using a twin-screw extruder at 150° C. and 100 rpm to obtain a CNF-reinforced PBAT composite material.

[0142] Then the composite material was dissolved in chloroform (the solid-liquid ratio of the composite material to chloroform was 1:10) and cast into a film. The solvent was then evaporated to obtain a composite material film with a dry film thickness of 30 μm.

[0143] Comparative Example 2-5: Preparation of lignin-enhanced PBAT film

[0144] 0.2% of ground wood lignin dry powder was added to the PBAT particles and mixed evenly, and then a twin-screw extruder was used to mix and extrude the particles at 150°C and 100rpm. The resulting pellets were then dissolved in chloroform (the solid-liquid ratio of the pellets to the chloroform was 1:10) and cast into a film, and then the solvent was evaporated to obtain a film with a dry film thickness of 30 μm.

[0145] Comparative Example 2-6: Preparation of PBAT film reinforced with lignin and CNF

[0146] 0.2 wt% of ground wood lignin dry powder and 1 wt% of dry CNF were added to the PBAT particles and mixed evenly, and then mixed and extruded into granules at 150°C and 100 rpm using a twin-screw extruder. The resulting pellets were then dissolved in chloroform (the solid-liquid ratio of the pellets to chloroform was 1:10) and cast into a film, and then the solvent was evaporated to obtain a film with a dry film thickness of 30 μm.

[0147] Comparative Example 2-7: Preparation of PBAT film

[0148] PBAT was extruded into pellets using a twin-screw extruder at 150°C and 100 rpm. The pellets were then dissolved in chloroform (the solid-liquid ratio of the pellets to the chloroform was 1:10) and cast into a film, and then the solvent was evaporated to obtain a film with a dry film thickness of 30 μm.

[0149] The cross section of the prepared composite film was observed by SEM, see Appendix Fig.12 .

[0150] Example 2-8: Testing the properties of the film

[0151] In this example, the force of the films obtained in Examples 2-1 to 2-5 and Comparative Examples 2-1 to 2-7 was tested.

[0152] Chemical properties, UV absorption properties, degradation properties and barrier properties.

[0153] Mechanical properties test: Referring to GB / T 1040.3-2006, the mechanical properties of the film were measured using a 3345 tensile tester (Instron, USA). The actual thickness of the test specimens was measured using a CT-100 thickness gauge. At least 7 specimens were prepared for each group, and the average value was taken. The tensile rate of the test was 50 mm / min.

[0154] UV absorption performance test: Characterized by UV-visible absorption spectrum, recording the transmittance of film samples in the range of 250-400nm. The UV absorption capacity of all films is normalized, and the UV absorption capacity of pure PBAT film is regarded as 0%.

[0155] Degradation performance test: Using a standard alkaline hydrolysis degradation method, the film was alkaline hydrolyzed with 0.5 mol NaOH solution at 58 °C for 72 hours, and the residual weight of each film sample was measured at a specific time point.

[0156] Barrier performance test: Refer to GB / T 12704.1-2009, use a test chamber and a moisture permeability cup to measure the film's moisture permeability WVP, the effective test area is 0.00283m 2 , the saturated vapor pressure at the test temperature is 6630Pa and the relative humidity is 90%.

[0157] The test results are shown in Tables 3 and 4 below.

[0158] Table 3

[0159]

[0160] Table 4

[0161]

[0162] The above results show that:

[0163] Compared with pure PBAT film (Comparative Examples 2-7), adding 1 wt% of esterified pre-treated PBAT film with in-situ dissociation

[0164] Functional lignocellulose is used as a reinforcing material, and is in situ dissociated into LCNF during the mixing process with PBAT, which can significantly improve the Young's modulus and ultraviolet absorption capacity of the film of the obtained composite material (Examples 2-1 to 2-5), and is positively correlated with the lignin content and the diameter of the LCNF;

[0165] Compared with Comparative Example 2-3 (i.e., the fiber with in-situ dissociation function after esterification pretreatment is first prepared into LCNF,

[0166] After drying, the film is mixed with PBAT to prepare a composite film). The film of Example 2-2 of the present invention has similar mechanical properties and ultraviolet absorption ability, which indicates that the LCNF is evenly dispersed in the composite material prepared by in-situ dissociation in Example 2-2, and the scheme of preparing PBAT / LCNF by in-situ dissociation in one step in Example 2-2 is obviously simple in operation process and lower in energy consumption;

[0167] Compared with the prior art films prepared in other comparative examples, the films prepared in the examples of the present invention have better mechanical properties.

[0168] This fully demonstrates that the LCNF with in-situ dissociation function after esterification pretreatment of the present invention is fully dispersed in the polymer matrix and thus effectively improves the mechanical properties and absorption properties of the polymer matrix, thereby significantly superior to the LCNF reinforced composite material prepared by the prior art method.

[0169] Compared with pure PBAT films (Comparative Examples 2-7), the films prepared in the embodiments of the present invention have better degradation performance and

[0170] The barrier properties are significantly better, which fully demonstrates that the LCNF with in-situ dissociation function of the present invention has good degradation performance, and its degradation ability is effectively improved after being compounded with the polymer matrix; the LCNF is fully dispersed in the polymer matrix, thereby effectively improving the barrier properties of the polymer matrix, which is significantly better than the LCNF-reinforced composite material prepared by the prior art method.

[0171] The above embodiments are only specific implementation methods of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principles of the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing wood nanocellulose, comprising: (1) dispersing a biomass raw material in a dibasic acid anhydride and greater than 0 to 5% water, performing an esterification pretreatment reaction at a pressure of 1 to 10 bar and a temperature of 20 to 120° C. to obtain a pretreatment reaction product, and washing the pretreatment reaction product to neutrality to obtain a neutral pretreatment reaction product; and (2) dispersing the neutral pretreatment reaction product in a medium and performing a dissociation treatment using a microfibrillation device to obtain a dispersion of wood nanocellulose.

2. The method according to claim 1, wherein in (1) the esterification pretreatment reaction, the temperature used is 30-120°C.

3. The method according to claim 2, wherein in (1) the esterification pretreatment reaction, the temperature used is 60-110°C.

4. The method according to claim 3, wherein in (1) the esterification pretreatment reaction, the temperature used is 80-100°C.

5. The method according to claim 1, wherein the biomass raw material is selected from wood, grass plants, crop straw, fruit shells and pine cones.

6. The method according to claim 5, wherein the biomass raw material is selected from bamboo, reed, rice straw, corn straw, wheat straw, sorghum straw, peanut shell, rice husk, pine cone, bagasse and coffee bean residue.

7. The method according to claim 1, wherein the dibasic acid anhydride is selected from malonic anhydride, maleic anhydride, dimethyl maleic anhydride, fumaric anhydride, succinic anhydride, methyl succinic anhydride, 2-hydroxysuccinic anhydride, (2-propylene) succinic anhydride, S-acetylmercaptosuccinic anhydride, cis-3-carboxyglutarate anhydride, trans-1,2-cyclohexanedicarboxylic anhydride, glutaric anhydride, adipic anhydride, cis-4-cyclohexene-1 ,2-dicarboxylic anhydride, cyclohexane-1,2-dicarboxylic anhydride, pimelic anhydride, suberic anhydride, azelaic anhydride, dodecylsuccinic anhydride, dodecenylsuccinic anhydride, phthalic anhydride, 4-chlorophthalic anhydride, tetrachlorophthalic anhydride, 3-fluorophthalic anhydride, 3,6-difluorophthalic anhydride, tetrafluorophthalic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride and citric anhydride.

8. The method according to claim 7, wherein the dibasic anhydride is selected from the group consisting of maleic anhydride, succinic anhydride, glutaric anhydride and phthalic anhydride.

9. The method according to claim 1, wherein the weight ratio of the biomass raw material to the dibasic acid anhydride is 5:1-1:

100.

10. The method according to claim 9, wherein the weight ratio of the biomass raw material to the dibasic acid anhydride is 1:1-1:

50.

11. The method according to claim 10, wherein the weight ratio of the biomass raw material to the dibasic acid anhydride is 1:4-1:

20.

12. The method according to claim 1, wherein in the esterification pretreatment reaction of (1), the water content is 2-5%.

13. A method for preparing a wood nanocellulose reinforced composite material, comprising: (1) dispersing a biomass raw material in a dibasic acid anhydride and greater than 0 to 5% water, performing an esterification pretreatment reaction at a pressure of 1 to 10 bar and a temperature of 20 to 120° C. to obtain a pretreatment reaction product, and washing the pretreatment reaction product to neutrality to obtain a neutral pretreatment reaction product; and (2) drying the neutral pretreatment reaction product and mixing it with a polymer matrix to obtain a wood nanocellulose reinforced composite material.

14. The method according to claim 13, wherein in the esterification pretreatment reaction of (1), the temperature used is 30-120°C.

15. The method according to claim 14, wherein in the esterification pretreatment reaction of (1), the temperature used is 60-110°C.

16. The method according to claim 15, wherein in the esterification pretreatment reaction of (1), the temperature used is 80-100°C.

17. The method according to claim 13, wherein the biomass raw material is selected from wood, grass plants, crop straw, fruit shells and pine cones.

18. The method according to claim 17, wherein the biomass raw material is selected from bamboo, reed, rice straw, corn straw, wheat straw, sorghum straw, peanut shell, rice husk, pine cone, bagasse and coffee bean residue.

19. The method according to claim 13, wherein the dibasic acid anhydride is selected from malonic anhydride, maleic anhydride, dimethyl maleic anhydride, fumaric anhydride, succinic anhydride, methyl succinic anhydride, 2-hydroxysuccinic anhydride, (2-propylene) succinic anhydride, S-acetylmercaptosuccinic anhydride, cis-3-carboxyglutarate anhydride, trans-1,2-cyclohexanedicarboxylic anhydride, glutaric anhydride, adipic anhydride, cis-4-cyclohexene- 1,2-dicarboxylic anhydride, cyclohexane-1,2-dicarboxylic anhydride, pimelic anhydride, suberic anhydride, azelaic anhydride, dodecylsuccinic anhydride, dodecenylsuccinic anhydride, phthalic anhydride, 4-chlorophthalic anhydride, tetrachlorophthalic anhydride, 3-fluorophthalic anhydride, 3,6-difluorophthalic anhydride, tetrafluorophthalic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride and citric anhydride.

20. The method of claim 19, wherein the dibasic anhydride is selected from the group consisting of maleic anhydride, succinic anhydride, glutaric anhydride and phthalic anhydride.

21. The method according to claim 13, wherein the weight ratio of the biomass raw material to the dibasic acid anhydride is 5:1-1:

100.

22. The method according to claim 21, wherein the weight ratio of the biomass raw material to the dibasic acid anhydride is 1:1-1:

50.

23. The method according to claim 22, wherein the weight ratio of the biomass raw material to the dibasic acid anhydride is 1:4-1:

20.

24. The method according to claim 13, wherein in the esterification pretreatment reaction of (1), the water content is 2-5%.

25. The method of claim 13, wherein the polymer matrix is ​​selected from the group consisting of polyethylene glycol, polyvinyl alcohol, polylactic acid, polybutylene adipate terephthalate, polybutylene succinate, polybutylene succinate-adipate, poly-ε-caprolactone, polymethylethylene carbonate, polyglycolic acid, butylene succinate-co-butylene terephthalate, polyethylene succinate-co-ethylene terephthalate, polyethylene succinate, polyurethane, polyamide, polycarbonate, polyoxymethylene, polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polyethylene naphthalate, polydiallyl terephthalate, polyparaben, and polyacrylonitrile.

26. The method of claim 25, wherein the polymer matrix is ​​selected from the group consisting of polybutylene adipate terephthalate, polylactic acid, and polyurethane.

Citation Information

Patent Citations

  • Nanocellulose as well as a preparation method and application thereof

    CN109867728A